Characteristics of gender socialization of adolescents in modern societies - Syrotjuk, K. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
This article considers the specific gender socialization of teenagers in contemporary society. Describes the basic socialization factors that determine the proper socialization. Also raised the item of gender identity and gender roles that affect the further development of the individual.